Effect of 5′‐adenosine monophosphate‐activated protein kinase agonists on insulin and glucose dynamics in experimentally induced insulin dysregulation in horses - Erin F. Pinnell; Laura D. Hostnik; Mauria R. Watts; Kathryn J. Timko; Allison A. Thriffiley; Mercedes R. Stover; Lauren E. Koenig; Olivia M. Gorman; Ramiro E. Toribio; Teresa A. Burns (Journal of Veterinary Internal Medicine, 2024)
Abstract Background 5′‐adenosine monophosphate‐activated protein kinase (AMPK) agonists, particularly resveratrol (RES), have not been extensively evaluated for their effect on insulin dysregulation (ID) in horses. Objectives Evaluate the effects of treatment with RES (10 mg/kg PO q12h), metformin (MET; 30 mg/kg PO q12h), and aspirin (ASP; 20 mg/kg PO q24h) on experimentally induced ID. Animals Thirty‐three healthy, adult, light‐breed horses. Methods Unblinded, placebo‐controlled, experimental trial evaluating effects of AMPK agonists (RES, MET, and ASP) on experimentally induced ID. Horses were randomly assigned to a treatment group (RES, MET/ASP, RES/ASP, RES/MET/ASP, or placebo [CON]) after induction of ID with dexamethasone (0.08 mg/kg PO q24h for 7 days). Frequently sampled insulin‐modified IV glucose tolerance tests (FSIGTT) and oral sugar tests (OST) were performed at baseline, 7 days after ID, and ID plus 7 days of treatment. Minimal model and OST variables were compared between (1‐way ANOVA) and within (1‐way ANOVA for repeated measures) groups over time to determine effects of treatment on ID. Results Administration of dexamethasone for 14 days resulted in significantly altered insulin and glucose dynamics (SI, DI, basal [glucose], and [insulin]) and produced clinical signs of laminitis in 5 out of 33 (15%) of horses included in the study. Combination therapy with RES, MET, and ASP did not significantly improve insulin and glucose dynamics in horses with experimentally induced ID. Conclusions and Clinical Importance Metabolic testing before glucocorticoid administration should be considered in horses with clinical signs of metabolic syndrome.